2021
DOI: 10.1111/inm.12906
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ attitudes towards alcohol use disorders and related issues: A comparative study in four American countries

Abstract: The present study identified and compared the attitudes of nursing students from North and South American countries towards alcohol, alcohol use disorders and persons with alcohol use disorders (AUDs). A cross-sectional design and survey approach were used. The sample consisted of 327 nursing students recruited from four nursing schools in metropolitan regions of North and South America. The questionnaire contained questions about sex, age, marital status, home country and other questions about training in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…We reviewed 201 full-text articles and excluded 167. We included 32 unique articles: 17 prevalence studies (in 17 articles) and 15 intervention studies (in 16 articles) 17–48 . Two articles described shorter- and longer-term outcomes of the same intervention study 24,25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed 201 full-text articles and excluded 167. We included 32 unique articles: 17 prevalence studies (in 17 articles) and 15 intervention studies (in 16 articles) 17–48 . Two articles described shorter- and longer-term outcomes of the same intervention study 24,25 .…”
Section: Resultsmentioning
confidence: 99%
“…All 17 observational studies included reported some HCP or trainee SUD stigma (Table 2; see Supplement Digital Appendix 5 at http://links.lww.com/ ACADMED/B473 for detailed quantitative results). Among studies that only assessed SUD stigma, stigma was either at the scale midrange 20,22,23,26,28 or lower than the scale midrange. 21,26,28,33,43,44 Among studies with comparison groups, stigma for SUDs was similar or worse than stigma for other chronic conditions.…”
Section: Prevalence and Extent Of Stigmamentioning
confidence: 99%
“…Latin American students' attitudes toward alcohol use are more negative than those of students from other cultures. Negative conceptions of alcohol and beverage use have been related to cultural beliefs and social attitudes common in this region (Heredia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The data breakdown phase was carried out by writing down 39 answers obtained from open-ended questions. Common themes among similar expressions were identified.…”
Section: Procedures and Samplesmentioning
confidence: 99%
“…Nurses who had previously worked with addicted individuals were asked an open-ended question about their attitudes and behaviors towards addicted colleagues. The data breakdown phase was carried out by writing down 39 answers obtained from open-ended questions. Common themes among similar expressions were identified.…”
Section: Data Analysesmentioning
confidence: 99%